Card tricks. - Fullman, Joe. (Laguna Hills, CA : QED, 2008)
"Includes step-by-step, illustrated instructions for 13 card tricks, plus performance tips and stories of famous magicians"--Provided by publisher.
Keywords: Card tricks --Juvenile literature